PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) BERBANTU MEDIA KANTONG AJAIB DALAM MENINGKATKAN KEMAMPUAN MENULIS CERITA PENDEK - Andy, Andy; Neni Triani, Susan; Yanti, Lili (Universitas Islam Sumatera Utara, 2023)
This research aims to determine the application of the Team Assisted Individualization (TAI) type cooperative learning model assisted by magic bag media in learning short story writing material in the odd semester of class IX of junior high school. In detail, the research objectives are to determine: (1) the ability to write short stories before and after implementing learning using TAI; (2) describe the implementation of the learning process using the Team Assisted Individualization (TAI) type cooperative learning model assisted by magic bag media, and (3) describe students' responses to the implementation of the Team Assisted Individualization (TAI) type cooperative learning model assisted by magic bag media in story writing material short. This research uses an experimental method in the form of a pre-experimental design with a one group pretest posttest design. The results of data analysis show that: (1) There is an increase in student learning outcomes in writing short stories between before and after the implementation of the Team Assisted Individualization (TAI) type cooperative learning model assisted by magic bag media with an average N-gain value of 0.67 in the category moderate, (2) The implementation of the Team Assisted Individualization (TAI) type cooperative learning model assisted by magic bag media in learning to write short stories is included in the good category with an implementation percentage of 79.54% and (3) Student learning responses after implementing the cooperative learning model The Team Assisted Individualization (TAI) type assisted by magic bag media to improve short story writing skills is included in the good criteria with a percentage reaching 88.7%. Thus, it can be concluded that the application of the Team Assisted Individualization (TAI) type cooperative learning model assisted by magic bag media can improve the ability to write short stories, the implementation of learning is carried out well and student responses are relatively good.